Vegetation analysis of spermatophyte in Taman Hutan Raya (Tahura) Seulawah, Aceh Besar - DJUFRI DJUFRI (Society for Indonesian Biodiversity, 2003)
The objectives of this study were to inventory of plant species, determine rank taxonomy of species, and to give informationquantitative value of taxa for vegetation analysis. About 5 hectare of the Tahura region is belong to Inhutani IV Company, was chosen as research population of this study. Two and half of hectare (2,5 ha) of this region used as a observed area. The data was collected by transec and quadratic method. The observed area it was took 10 transec with 250 m of long for observed stations. Each observed station was put six quadratic sampels systematically. Each quadratic sampels has a 2,5 m2 of width. The parameter search is the total species. The result of this study indicated that there were 66 species of the plant including 29 family. Diversity index was between 2.3896-3.4696, an evenness index was between 1.7331 unto 211.5479. Based on this data, it can be conducted that every family of the plant has a few species. The important value is relatively low on all stations observed. So that there is no evident showing, any dominant species of the plant in observed area. Diversity index was categorized medium (> 2 - 4). Diversity index can be used as indicator were the vegetation succession. Evenness index of each station was relatively low, because sum of species were varied. Similarity index was below 50%. The differences might be the results of several factors including variety of physical environment, chemical content of soil, and interaction inter species in observed area.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: vegetation, diversity index, Tahura Seulawah